День закрытых дверей: роман / Ирина Левит - Левит Ирина Семеновна (Военные приключения, 2021)
Экземпляры: (20220928) / Инвентарный номер: 63923 / Цена: 291.00 / Сис.шифр: Р2 / Авт.знак: Л 36 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6